The Effect of Implementing the Problem Based Learning Model Using Digital Platforms on the Success of Learning Accounting - Kuswanto, Kuswanto; Silaban, Erika Sabatany; Putra, Iwan; Liputo, Muhammad Arif (Perspektif Pendidikan dan Keguruan, 2024)
Learning accounting not only requires students to master accounting concepts but also requires mastering skills in managing financial information in an accounting system. Accounting learning requires an effective model that focuses on students who can practice their skills and develop their knowledge, namely the "Problem-Based Learning" (PBL) model. This research seeks to examine the effect of implementing the PBL model using digital platforms on student learning success. The subjects of this research were class XII students at Public High School 13 Jambi City. The research was conducted using a "Quasi Experiment" model with a "non-equivalent control group" design, namely using an experimental class and a control class. Research data is the result of learning before and after implementing the PBL model using the Digital Platform which is rationed in the form of an N-Gain score. Data were analyzed using the statistical technique "comparative independent sample t-test". Based on the analysis results, the average N-Gain score for the experimental class was 52.32 in the quite effective category, and the average N-Gain score for the control class was 37.17 in the ineffective category. The results of the "independent sample t-test" obtained a calculated t-value of 4.287 > compared to the t table at alpha 5% of 2.00 so that the application of the PBL model with the use of digital platforms in accounting learning was proven to have a significant effect on the learning success of students at " Public High School 13 Jambi City”. The application of the PBL model by utilizing digital platforms is an alternative to optimizing accounting learning in the current era of digitalization of learning.